The world the game theorists made - Erickson, Paul, 1976- (The University of Chicago Press, 2015)
In recent decades game theory - the mathematics of rational decision-making by interacting individuals - has assumed a central place in our understanding of capitalist markets, the evolution of social behavior in animals, and even the ethics of altruism and fairness in human beings. With game theory's ubiquity, however, has come a great deal of misunderstanding. Critics of the contemporary social sciences view it as part of an unwelcome trend toward the marginalization of historicist and interpretive styles of inquiry, and many accuse its proponents of presenting a thin and empirically dubious view of human choice.